The Art of Memory : The Loss of History. - Olander, William; Williams, Reese; Deitcher, David (New York : The New Museum of Contemporary Art, 1985)
Barber, Bruce ; Barry, Judith ; Brauntuch, Troy ; Charlesworth, Sarah ; Lawler, Louise ; Lhotsky, Tina ; Piper, Adrian ; Prina, Stephen ; Prince, Richard ; Rosler, Martha ; Santos, René ; Sugimoto, Hiroshi ; Williams, Christopher
The Art of Memory : The Loss of History, The New Museum of Contemporary Art, New York, November 23, 1985 - January 19, 1986
boek